2014
DOI: 10.1021/jf404766f
|View full text |Cite
|
Sign up to set email alerts
|

Investigating C-4 Sugar Contamination of Manuka Honey and Other New Zealand Honey Varieties Using Carbon Isotopes

Abstract: Carbon isotopes (δ(13)C honey and δ(13)C protein) and apparent C-4 sugar contents of 1023 New Zealand honeys from 15 different floral types were analyzed to investigate which New Zealand honey is prone to failing the AOAC 998.12 C-4 sugar test and evaluate the occurrence of false-positive results. Of the 333 honey samples that exceeded the 7% C-4 sugar threshold, 324 samples of these were New Zealand manuka honey (Leptospermum scoparium, 97.2% of all fails found in the study). Three monofloral honeys (ling, ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
0
16
0
2
Order By: Relevance
“…Interestingly, perceived unadulterated New Zealand manuka honeys routinely fail the AOAC adulteration test, especially manuka honeys with high antimicrobial activity (Rogers et al 2010(Rogers et al , 2013 and similar situations have been reported in other European honeys (White 1992;Cotte et al 2007). To date, the factors underpinning this phenomenon are largely unexplained; however, work done by Rogers et al (2010Rogers et al ( , 2013Rogers et al ( , 2014a has clearly shown that in many cases the current official methods (AOAC, 1999) are not sufficiently sensitive for C 4 level detection in some honeys and have called for a revision to the accepted protocols.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, perceived unadulterated New Zealand manuka honeys routinely fail the AOAC adulteration test, especially manuka honeys with high antimicrobial activity (Rogers et al 2010(Rogers et al , 2013 and similar situations have been reported in other European honeys (White 1992;Cotte et al 2007). To date, the factors underpinning this phenomenon are largely unexplained; however, work done by Rogers et al (2010Rogers et al ( , 2013Rogers et al ( , 2014a has clearly shown that in many cases the current official methods (AOAC, 1999) are not sufficiently sensitive for C 4 level detection in some honeys and have called for a revision to the accepted protocols.…”
Section: Discussionmentioning
confidence: 85%
“…Further reasons for the possible misclassification of honeys as ‘adulterated’ may result from the improper storage of honey at high temperatures, that is, > 27·0°C (Rogers et al . ,b). Although in this study all honeys were stored at ~20°C, the possibility of higher storage temperatures prior to arrival at the laboratory cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the manuka samples had δ 13 C honey values of −25.13‰ and −25.58‰ respectively, which is inconsistent with Rogers et al . 45 who suggested that δ 13 C values in authentic manuka honey should not be less than −24.7‰. Therefore, the multiple criteria used here to assess honey authenticity indicates that both the manuka honey samples analysed were non-authentic products.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, gas chromatography 6,7 and high-performance liquid chromatography [8][9][10][11][12][13] are also used to detect adulterated honey samples. Moreover, carbon isotope ratio (C 12 /C 13 ) analysis [14][15][16][17][18][19][20] (IR-MS) is used as a standard technique to detect the presence of artificial sweeteners in honey. Although there has been a great deal of study in the literature, IR-MS analysis requires more elaborate sample preparation techniques and therefore takes a lot of time.…”
Section: Introductionmentioning
confidence: 99%